Peran Peran Status Sosial Ekonomi dalam Mempengaruhi Performa Akademik Peserta Didik di SD Negeri 1 Pogung - Mawadah, Nurfina; Hardhiyani, Nuri Romi; Faqihuddin, Nurrahmad; Safitri, Nurul; Dewi, Oktafiani Shandra; Annisa, Rahma; Susanti, Maria Melani Ika (Jurnal PGSD, 2025)
Based on teacher information, most students at SDN 1 Pogung have low socio-economic backgrounds. Students’ learning achievement tends to be low because their parents are more focused on working to meet their living needs, so that parental involvement ini guiding children to study at home is limited. Based on these findings, researchers are interested in conducting research to reveal the role of socio-economic status in influencing students’ academic performance in Elementary School. The type of research used in this study is descriptive qualitative research. Data in this study were collected through interviews and documentation studies of relevance secondary sources, such as documents, journals, and books. The results of this study indicate that socio- economic status has a significant impact on students’ academic development. Factors such as access to educational resources, parental involvement, and environmental conditions greatly influence their learning performance. Therefore, an inclusive learning strategy and personal approach are needed so that each student gets equal learning opportunities. In this study, an in-depth analysis has been carried out on the influence of economic status on students’ learning achievement performance at SD Negeri 1 Pogung. The results of the study showed a significant relationship between students’ economic conditions and their academic performance. In general, students who come from families with lower economic status tend to have poorer learning achievements compared to students from better economic backgrounds.